KERAGAMAN HAMA DAN MUSUH ALAMI PADA PERTANAMAN GENERATIF KEDELAI (Glycine max L. Merr) DENGAN KERAPATAN TANAMAN YANG BERBEDA - As'ari As'ari; Helda Orbani Rosa; Chatimatun Nisa (Universitas Lambung Mangkurat, 2019)
Soybean production in Indonesia still relatively low, even though the demand for soybean in every year has increased with increasing growth population, however the demand for soybeans is unable to balance domestic production, so it must be imported in a huge amount (Ohorella, 2011). To increase soybean production is certainly not always dependent in using of chemicals, by using suitable plant spacing can reduce the growth of pests naturally, natural enemies of pests also play a role in suppressing the growth of pests, therefore it is necessary to set different of plant spacing to knowing the best spacing for suppresing pests naturally. The purpose of this research was to determine the types of pests and natural enemies in the generative period of soybean plants and to determine the effect of different spacing on pest and natural enemies diversity. This research use Randomized Block Design (RAK) 1 Factor with 5 types of treatment spacing (20 x 20 cm, 20 x 30 cm, 20 x 40 cm, 20 x 50 and 20 x 60 cm) and 5 replications so that there are 25 experimental units. The results showed that plant spacing significantly affected pest diversity, but did not significantly affect the diversity of natural enemies, in this research, the best plant spacing to suppress pest growth was treatment with a spacing of 20 x 30 cm.